2012
DOI: 10.5812/hepatmon.6191
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of DNA Sequence in the Basal Core Promoter, Precore, and Core Regions of Hepatitis B Virus from Tunisia Shows a Shift in Genotype Prevalence

Abstract: BackgroundIn this study, we evaluated the prevalence of the most common mutations occurring in Enhancer II (EnhII), Basal Core Promoter (BCP), Precore (PC), and Core (C) regions of hepatitis B virus (HBV) genome.ObjectivesWe also investigated the correlation between HBV variants, their genotypes, and patients’ HBe antigen (HBeAg: soluble shape of the capsid antigen) status.Patients and MethodsWe retrieved viral DNA from 40 serum samples of Tunisian patients positive for hepatitis B surface antigen (HBsAg) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…Similarly, all sorts of PC mutant variants so far described and functionally known as the start codon mutations (A1814C/C1816; 15.4%) that abolish HBeAg expression [ 33 ] and G1862T (44.8%) mutation that interferes with post-translational modification of the HBeAg-precursor [ 34 , 35 ] were most common. Interestingly, the premature stop codon (G1896A) that is known to abolish the synthesis of HBeAg [ 36 , 37 ] in particular with C1858T was found to be 21.7% and commonly found in subjects with genotype D. In addition, finding a case with no multiple mutations from BCP and PC genes were difficult in the current study. However, the observation of the inverse relationship between the BCP double mutations and PC stop codon mutation was in line to a study that reported the co-existence of PC stop codon mutation might influence the BCP mutations [ 38 ].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Similarly, all sorts of PC mutant variants so far described and functionally known as the start codon mutations (A1814C/C1816; 15.4%) that abolish HBeAg expression [ 33 ] and G1862T (44.8%) mutation that interferes with post-translational modification of the HBeAg-precursor [ 34 , 35 ] were most common. Interestingly, the premature stop codon (G1896A) that is known to abolish the synthesis of HBeAg [ 36 , 37 ] in particular with C1858T was found to be 21.7% and commonly found in subjects with genotype D. In addition, finding a case with no multiple mutations from BCP and PC genes were difficult in the current study. However, the observation of the inverse relationship between the BCP double mutations and PC stop codon mutation was in line to a study that reported the co-existence of PC stop codon mutation might influence the BCP mutations [ 38 ].…”
Section: Discussionmentioning
confidence: 57%
“…These could also be an indication of a wild-type mixed HBV viral population infection, but with BCP/PC mutant variants [ 39 ]. In addition, the development of such mutant variants in both HBeAg positive and negative case could be the result of the synergistic effect of different mutation profiles or genotype differences [ 37 , 40 ]. In the current study, such mutant profiles were particularly seen in association with genotype D except for the double BCP mutations.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this viral genomic stability, it was necessary to explain the variation in HBV genomic sequences after intrafamilial transmission occurred. In this sense, it is necessary to consider that HBV isolates from genotype D1 appear to be prone to mutations in BCP‐PC regions . For that reason, two genomic regions were targeted for amplification, sequencing and phylogenetic inferences.…”
Section: Discussionmentioning
confidence: 99%
“…In Bolivia, the exchange of native HBV subgenotype F4 and exotic ones (subgenotypes B2 and C2) between Bolivian and Japanese immigrants was clearly demonstrated by phylogenetic analysis [151] . Interestingly, the exotic strains have different mutational patterns in different ORFs of HBV [123] , which would have a different impact on the course of infection, therapeutic, diagnostic and prophylactic measures [152,153] .…”
Section: Effect Of "Immigro-subgenotype" On Clinical Outcomementioning
confidence: 99%
“…Although the genotype D of HBV is distributed globally, its subgenotypes are locally confined to certain geographical regions. For example, subgenotype D1 is restricted to Iran and its neighboring countries [116,[122][123][124][125][126] . Subgenotype D2 is derived from East Europe and Russia, D3 was detected in Serbia, South Africa and Alaska, D4 was found in Oceania and Somalia, and D5-D9 were reported from India, Indonesia Tunisia and Nigeria [67] .…”
Section: Hbv Subgenotypes and Geographical Distributionmentioning
confidence: 99%